Methodology to Prepare Patent Analysis and the Technological Maturity Cycle (2023)
The analysis of patents and the behavior of technology over time have aroused great interest at institutions and companies because they serve as a guide to make decisions on research and innovation projects. Based on this, a methodology that seeks to guide the reader in the preparation of this type of study; both the body of the document and its interpretation has been developed. Two software were used to describe the extraction of patent data; Orbit Intelligence (Licensed Software) and Lens (Open access version). The information obtained, using the same search equation, was presented. For the analysis of the technological maturity cycle, the logistic model was obtained, and it was executed in the Loglet Lab 4 software to obtain the growth curve S. Finally, the Yoon parameters were presented to give a predictive concept of the behavior of the technology over time. The case study that was taken as an example was the technology of “Antibacterial and self-cleaning surfaces based on TiO2/ZnO”, which applied this methodology,  we found that the technology of interest is in the maturity phase. It has a high impact on the market, being an important indicator for decision-making focused on research and development. According to what has been proposed, the exposed methodology is a tool to have in consideration that allows to present a more accurate concept about the future projections of a technology, based on the analysis of patent data. Moreover, it is important to consider the trends of the market and the socio-political situation.